2016
DOI: 10.1007/s11011-016-9930-y
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampus-specific deficiency of IL-15Rα contributes to greater anxiety-like behaviors in mice

Abstract: A hippocampus-specific IL15RαKO mouse (hipIl15ra /Cre) was generated to test the hypothesis that the targeted deletion of interleukin-15 receptor alpha (IL-15Rα) in the hippocampus contributes to altered behavior, including greater levels of anxiety and ambulatory activity. Using Cre-loxP, exons 2 and 3 of the IL-15Rα gene were excised within the hippocampus, while normal expression was maintained within the rest of the brain. In the open field test (OFT), hipIl15ra /Cre spent a greater amount of time in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Several published reports have confirmed that IL-15Rα insufficiency results in multiple disorders, including but not limited to immunodeficiency, skeletal muscle variations, and a range of neurological symptoms (24,(50)(51)(52)(53)(54). The presence of inflammation is an essential etiological hypothesis in psychiatric diseases, including schizophrenia and depression, and we observed alterations in the serum levels of IL-15Rα in patients with schizophrenia and depression in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Several published reports have confirmed that IL-15Rα insufficiency results in multiple disorders, including but not limited to immunodeficiency, skeletal muscle variations, and a range of neurological symptoms (24,(50)(51)(52)(53)(54). The presence of inflammation is an essential etiological hypothesis in psychiatric diseases, including schizophrenia and depression, and we observed alterations in the serum levels of IL-15Rα in patients with schizophrenia and depression in this study.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, injured female mice in this model display more anxiety-like behavior in the open field performance, and TH does not provide protection in this testing domain either. Although mice have a natural tendency to explore the periphery more than the unprotected center areas while in the open field, mice with anxiety like behavior spent even more time in the periphery than the center than did shams [80,81]. Congruent with these findings, a higher prevalence of anxiety disorders and increased impulsivity and compulsivity characterize HIE survivors [82].…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine/myokine IL15 and its primary binding partner IL15RA, besides their well-studied role in T and natural killer (NK) cell physiology, participate in the regulation of energy processes in a variety of other tissues (He et al, 2010), including brain (Wu et al, 2010;Nguyen et al, 2017), bone (Djaafar et al, 2010;Loro et al, 2017) and muscle (Quinn et al, 2013;Pistilli et al, 2011;Loro et al, 2015). Fast muscles of mice lacking IL15RA (Il15ra −/− ) are fatigue resistant (Pistilli et al, 2011) and their mitochondria more efficiently oxidize fatty acids as primary energy fuel (Loro et al, 2015).…”
Section: Introductionmentioning
confidence: 99%